2005
DOI: 10.1089/mdr.2005.11.309
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Drug-Resistant Clones ofStreptococcus pneumoniaeColonizing Healthy Children in Portugal

Abstract: A total of 3,539 Streptococcus pneumoniae (Pn) were recovered from 4,969 nasopharyngeal samples of children attending 13 day-care centers (DCCs) located in Lisbon, Portugal, during a surveillance study from January, 2001, through March, 2003, integrated in the European intervention project (EURIS, European Resistance Intervention Study). All Pn isolates were tested for anti-biotyping and drug-resistant pneumococci (DRPn) were further tested by serotyping and pulsed-field gel electrophoresis (PFGE). Overall car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…Antibioticresistant isolates obtained between 1996 and 2003 were characterized before (19,21,33,37). Isolates obtained in 2006 were partially described (according to their serotypes) before (29), and isolates obtained in 2007 are first described in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibioticresistant isolates obtained between 1996 and 2003 were characterized before (19,21,33,37). Isolates obtained in 2006 were partially described (according to their serotypes) before (29), and isolates obtained in 2007 are first described in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Signed informed consent was obtained from the parents or guardians of participating children. This study design for sampling has been maintained for several years, allowing direct comparisons over time (19,21,33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous point prevalence studies conducted among Portuguese DCC attendees have found high pneumococcal and H. influenzae colonization rates (over 70%) (5,12) with abundant representation of international clones (22).…”
mentioning
confidence: 92%
“…Os principais fatores que influenciam a taxa de colonização nos portadores incluem: idade abaixo de dois anos, número de irmãos e condições de aglomerações, ou seja, condições de vida em pequenas áreas, particularmente em creches (MALFROOT et al, 2004;MATO et al, 2005).…”
Section: Colonização E Fatores De Riscounclassified